2018
DOI: 10.1152/ajpgi.00101.2018
|View full text |Cite
|
Sign up to set email alerts
|

Ground flaxseed reverses protection of a reduced-fat diet against Citrobacter rodentium-induced colitis

Abstract: Flaxseed is high in omega-3 polyunsaturated fatty acids, fiber and lignans known to lower cholesterol levels. However, its use for prevention or treatment of inflammatory bowel diseases has yielded mixed results, perhaps related to dietary interactions. In this study, we evaluated the impact of ground flaxseed supplementation on the severity of Citrobacter rodentium-induced colitis in the setting of either a high fat (HF; ~36 %kcal) or reduced fat (RF; ~12 %kcal) diet. After weaning, C57BL/6 mice (n=8-15/treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 56 publications
0
16
0
1
Order By: Relevance
“…Manipulation of lipid content in host tissues, including omega-6 PUFAs such as arachidonic acid (C 20:4 ) and omega-3 PUFAs such as alpha-linoleic acid (C 18:3 ), eicosapentaenoic acid (C 20:5 ), and docosahexaenoic acid (C 22:6 ), through dietary, genetic, or pharmacological interventions is associated with altered severity of disease in numerous experimental models of colitis (55,56). In the context of enteric bacterial infection, the administration of different dietary oil supplements can alter disease outcomes in mice challenged with Citrobacter rodentium, a murine pathogen that serves as an established model for human EHEC and enteropathogenic E. coli (EPEC) infection (57)(58)(59)(60)(61). Given the high fat content and increased omega-6-to-omega-3 ratios characteristic of the Western diet, there is much interest in defining the molecular mechanisms by which specific PUFAs may modulate the outcomes of intestinal diseases such as enteric infection.…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation of lipid content in host tissues, including omega-6 PUFAs such as arachidonic acid (C 20:4 ) and omega-3 PUFAs such as alpha-linoleic acid (C 18:3 ), eicosapentaenoic acid (C 20:5 ), and docosahexaenoic acid (C 22:6 ), through dietary, genetic, or pharmacological interventions is associated with altered severity of disease in numerous experimental models of colitis (55,56). In the context of enteric bacterial infection, the administration of different dietary oil supplements can alter disease outcomes in mice challenged with Citrobacter rodentium, a murine pathogen that serves as an established model for human EHEC and enteropathogenic E. coli (EPEC) infection (57)(58)(59)(60)(61). Given the high fat content and increased omega-6-to-omega-3 ratios characteristic of the Western diet, there is much interest in defining the molecular mechanisms by which specific PUFAs may modulate the outcomes of intestinal diseases such as enteric infection.…”
Section: Discussionmentioning
confidence: 99%
“…AO dose‐dependently increases plasma and mononuclear levels of ALA, ETA, and DPA, and enhances interleukin‐10 expression in response to LPS . We previously reported that whole flaxseed reverses the protective effects of a reduced fat diet on C. rodentium colitis at a dose similar to the n ‐3 PUFA oil content tested here . Importantly, the present study suggests that the observed negative effects were not due to flaxseed meal oil content per se, but rather due to other components present in the seed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 5% flaxseed supplemented diet had no protective effect against the development of intestinal tumours [83]. Caution in the use of flaxseed in the diet has also been introduced by the results of Maatanen and co-workers, who showed that whereas a reduced fat diet could protect against colitis, the high levels of PUFAs provided by flaxseed supplementation to the diet diminished these beneficial effects [84].…”
Section: Dietary Flaxseed and Gastro-intestinal Healthmentioning
confidence: 99%